Cinematography in the Novel City of Images - Hussein, Dr. Safaa Abdul-Kadhim (Thi Qar Arts Journal, 2023)
The novel is a literary genre based on written language. It is founded on the element of narration primarily, which meets in most cases with the element of description, where they form together an extension governed by an event structure based on the sequence of causes and their effects, as Todorov suggests. In addition to the existence of a narrator, characters, spaces and times, it thus meets with a group of other literary genres in this aspect, such as the genre of the tale and the story.But what distinguishes it is that it is a literary genre capable of containing various other genres and melting them in its structure. The novel is no longer represented by that horizontal sequential line of the tale, but sought to merge with other arts that worked to feed the units of narration with new cards, and to provide them with vital elements that increase their artistic effectiveness and move them to innovative work spaces that multiply their creative possibilities.